Rancang Bangun Aplikasi Laporan Keuangan pada CV. Budi Mandiri - Rachmanto, Wahyudi; Slamet, Slamet; Mastan, Ignatius Adrian (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
CV. Budi Mandiri is a company engaged in the services sector that was built in 2005 at Pakis 86 Surabaya. At the inception of a company stand, the owner of CV. Budi Mandiri only handle a request driving course, but over time, CV. Budi Mandiri open a business as the Salon car or washing polishes car. Business activity in the CV. Budi Mandiri are driving course registration and payment, sales of car polish cleaning services, and payments of cash or purchase equipment polishing car wash. For process reporting a transaction is still recorded manually. The owner did not know the income received for never making a finance report in detail. The waterfall model is one method of system development SDLC (System Development Life Cycle) that are typical in the execution of each phase, each phase of the waterfall must be completed before proceeding to the next development phase. Waterfal model used in application design financial reports on the CV. Budi Mandiri .And stages through Waterfall models are determination and specification analysis, system design, implementation and unit testing, integration and system testing, and operation and maintenance. Report Finance Aplication is a system that can archive data on revenues and cash expenditure company. Furthermore, Â the output generated application of financial report are a general journal report, ledger, income statement, statement of changes in equity, and the balance sheet.Keywords : Waterfall model, System Development Life Cycle,Finance Report